Contribution to investigation of correlation between hardness and wear resistance at austempered ductile iron - Kakaš, Damir; Paljić, Damir; Škorić, Branko; Bajić, Vladimir (Journal of Production Engineering, 1992)
In this paper, the correlation between hardness and wear resistance in austempered ductile iron was investigated. Different types of structures in the samples were produced by varying the parameters of heat treatment. Wear resistance was examined using the universal testing machine Amster, applying high specific loads during the roll with 10% sliding. The intensity of wear was controlled by measuring the loss of weight and changes in wear surface hardness. The morphology of the wear surface was investigated by scanning electron microscopy. The influence of heat treatment parameters on the structure of austempered ductile iron was analyzed by light microscopy and also by scanning electron microscopy on the fracture surface. The results show that there is a significant influence of hardness, but in specific cases within the group of samples with very similar hardness (but with differences in structure), significant differences in wear resistance appear.